Atypical presentation of a rare gestational trophoblastic neoplasm: a case report - Binte Aamir, Faiqa; Raza Raja, Mohummad Hassan; Ahmad Zaidi, Syeda Maria; Aahil Noorali, Ali; Bin Pervez, Mohammad; Hasnain Fatimi, Saulat (Journal of the Pakistan Medical Association, 2022)
A 34-year-old woman had a history of 3 miscarriages and presented with symptoms of an unproductive cough and rising serum beta-human chorionic gonadotropin (B-hCG) levels. There were no gynaecological symptoms. A diagnosis of Choriocarcinoma with pulmonary metastasis was made. In Pakistan, the incidence of Choriocarcinoma remains exceedingly rare, accounting for less than 0.3% of all gynaecologic tumours. Though rare, if managed appropriately, it has a reasonably good prognosis, as demonstrated by the outcome of the current case. Keywords: Choriocarcinoma, EMA-CO Chemotherapy, Pulmonary Metastasis, Thoracotomy